A rapid label- and enzyme-free G-quadruplex-based fluorescence strategy for highly-sensitive detection of HIV DNA. Issue 1 (19th November 2019) - Zhang, Feng; Xiang, Ling; Xiao, Xianghui; Chen, Xiaoming; Chen, Chunyan; Cai, Changqun
Abstract : Because rapid and selective methods for HIV detection are urgently needed, herein, a simple label- and enzyme-free strategy is constructed for fluorescence detection of HIV DNA. Abstract : Because rapid, convenient, and selective methods for HIV detection are urgently needed, herein, a simple label-free and enzyme-free strategy is constructed for sensitive fluorescence detection of HIV DNA using the fluorescent intercalating dye thioflavin T (THT) as the detection signal source. This strategy utilizes a hairpin DNA sequence (H1) and two assistant strands. H1 is wisely designed with a G-quadruplex sequence in the stem. Target DNA, when present in solution, will hybridize with H1 to form H1/target duplexes and release the G-quadruplexes. Additionally, the assistant probes hybridize with the unfolded H1 to form a stable DNA double strand, resulting in the displacement of the target to participate in another similar reaction cycle. Consequently, many G-quadruplex structures are generated, leading to a significantly amplified fluorescence signal of THT. The linear range is from 0.1 nM to 50.0 nM with a limit of detection of 13 pM. Results can be achieved within 40 min, because the cyclic amplification involves only one DNA hairpin and two auxiliary chains. Furthermore, this platform exhibited good selectivity with one base mismatch or other DNA sequences. This strategy could be used as a simple, sensitive, and selective tool to detect other DNA biomarkers.